2009
DOI: 10.4067/s0716-97602009000400002
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of crude ethanol extract and fractions of Eugenia uniflora (Myrtaceae) in the hepatopancreas of Oreochromis niloticus L

Abstract: This study evaluates the bioactivity of the crude ethanol extract and ethyl acetate, hexane and chloroform fractions obtained from Eugenia uniflora leaves using the hepatopancreas of Oreochromis niloticus L. as an experimental model. The ethanol extract and fractions were administered to the fish orally with their feed. Twenty-four hours later, the fish were sacrificed and their livers dissected, fixed in neutral formalin, embedded in paraffin and sectioned. Histological analyses were performed using Masson's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(10 reference statements)
0
3
0
1
Order By: Relevance
“…Its aerial parts present many pharmacological properties, including anti-giardial (Brandelli et al, 2009), antimicrobial (Holetz et al, 2002;Coelho de Souza et al, 2004), and toxicity in fish hepatopancreas (Fiuza et al, 2009). So far, no reports have been found of antitumor activity or lethality in brine shrimp bioassay.…”
Section: Discussionmentioning
confidence: 99%
“…Its aerial parts present many pharmacological properties, including anti-giardial (Brandelli et al, 2009), antimicrobial (Holetz et al, 2002;Coelho de Souza et al, 2004), and toxicity in fish hepatopancreas (Fiuza et al, 2009). So far, no reports have been found of antitumor activity or lethality in brine shrimp bioassay.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al, 1997 reported eugeniflorin D1 and eugeniflorin D2, as well as two hydrolysable macrocyclic tannins, in the leaf methanolic extract of Eugenia uniflora. Previous reports on the essential oils of Eugenia uniflora indicated presence of selina-1, 3, 7(11)-trien-8-one, germacrone, furanodiene and curzerene (Fiuza et al, 2009;Thambi et al, 2013). Here we report the antimicrobial properties of the methanolic extract, three test fractions and essential oil from the fresh leaves of Eugenia uniflora on Klebsiella pnemoniae and Trichophyton rubrum for the first time.…”
Section: Introductionmentioning
confidence: 94%
“…Fresh and dried leaves of E. uniflora is reported in folk medicine for treating cough, bronchitis, diarrhoea, influenza, rheumatism, fevers, inflammatory and stomach diseases (Consolini and Sarubbio, 2002;Costa et al, 2009;Fiuza et al, 2009;Lago et al, 2010 andSouzaMoreira et al, 2010). In Nigeria, E. uniflora leaves have been reported for antimalarial activities (Famuyiwa and Adebajo, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…5 Essa espécie é utilizada na medicina popular na forma de sucos, infusões e decocções das folhas e raízes, devido às propriedades citotóxica, antifúngica, anti-reumática, anti-inflamatória, antimalárica e antiulcerativa. 6 A micose sistêmica humana paracoccidioidomicose atua como doença pulmonar primária, frequentemente assintomática, disseminável, e que resulta da inalação de conídios do fungo dimórfico Paracoccidioides brasiliensis, encontrados no solo e em plantas nas regiões subtropicais da América Latina. Esta doença acomete principalmente trabalhadores do sexo masculino em fase produtiva, especialmente em zonas rurais da região centro-oeste, considerada um centro de endemia de paracoccidioidomicose.…”
Section: Introductionunclassified